Designing processors of the structure of the word of majesty to Kufic calligraphy (analytical Study) (Journal of the College of Basic Education, 2022)
The art of the Arabic calligraphy has evolved and developed under the Islamic civilization, and it has spread and contributed to its intuitions and care of the Arab and Muslim calligraphy, which showed the diversity of its artistic structures according to its functional, esthetic and intercultural levels and according to the rules and technical standards that demonstrated their commercial skills and the specificity of this art. Among the most prominent of these artistic phenomena are (the art of composition), which came as a result of the adaptation of characters and sections to the selected bodies, which allowed for the creation of design treatments for the art of linear composition according to all bodies, including the selection of the word "God", his Majesty, and the sanctity of the word "in the Kufic calligraphy. It has expanded creatively for many of the plans.and in the midst of this trend of research in the study "Designing processors of the structure of the word of majesty to Kufic calligraphy (analytical Study)" which included four chapters, the first chapter included the problem of research, its importance, objectives, limits and terminology. The second chapter contained four detectives, the first dealt with the Calligraphy compositions (Genesis and Evolution), and the second to identify the design treatments for Calligraphy compositions, while the third research to track the factors that help with the diversity of for Calligraphy compositions, and the fourth research to follow the Kufic Calligraphy came, while the third chapter came to represent the search procedures based on the analytical descriptive approach, and the knowledge of the number of the society that reached (32) written structure of the word of majesty. A sample was taken intentionally to reflect its characteristics, and the total sample (4) was a model analyzed. The analysis concluded with a number of findings, Chapter 4, which listed the design treatments of (balance, contrast and contrasting, proportion, symmetry, frequency and rhythm, and sovereignty), which are the basic regulations in attracting the recipient to synthesize the structures of the word of majesty, through all sample models, as well as the appearance of the effective in the Kufic calligraphy in the recipient also appears. In particular, the support of the exhalation to enhance its distinctive design structure, which expressed the intuitive beauty of the plans, skill, mechanization, expressive capability, and the investment of all the sample lines, for the factors that help to diversify the linear structures represented by (tides and variations, technical compositions, intersections and overlap, character variations, acceptance of decorative additions), not just for a esthetic aspect. It's a complementary job performance to exit with new configurations, which have returned as a visual polarization and esthetic value.The study recommended that use be made of the design of the composer's compositions in order to create and renew written compositions in general, and to include the courses on Arabic calligraphy, which focus on the implementation of the composer's semantics. Especially in the Arabic calligraphy and decoration department in the Faculty of Fine Arts and the corresponding sections in other colleges. The study proposal for the study of the design treatments for the compositions of all the lines of the term (analytical study) should be addressed